PERLUNY A EVALUASI KINERJA PARASITOID PADA HAMA DAUN KELAPA : BRONTISPA LONGISSIMA GESTRO (COLEOPTERA: CHRYSOMELIDAE) DI KABUPATEN ENDE-FLORES - Sri Wahyuni (Agriculture Faculty of Flores University, 2008)
Brontispa longissima Gestro (Coleoptera: Chrysomelidae) is ones of the most important pest who attack of many family palms in South East Asia. In Indonesia, Brontispa longissima has. becomes a primer pest on coconut. It was Decreasing yield result up to 30 - 40 % returns and 5% of the attacked crops will die. Ones of the failed reason of control action is a low preventive system on every territory entrance, otherwise, coconut was a needful and fast-moving commodity for people and industry. The second reason is secondary commodity assumes and low cropping system caused pest and disease uncontrolled. Three bio-control usages on-field need to monitored caused farmers incapable. The success indicator for parasitoid release was quick and easy to adapt for the parasitoid. It was related